Managing odour pollution from livestock sources in Malaysia: Issues and challenges - Zaini Sakawi,; Lukman Ismail, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Odour pollution from livestock farms can adversely affect quality of life and human environment. There is a dearth of study on this type of odour pollution in Malaysia despite its relatively widespread media coverage. The impact of such pollution not only created inconveniences but also exposed the surrounding population to certain diseases. This study highlighted some of the salient issues and challenges related to livestock-originated odour pollution management in Malaysia. Enhanced monitoring of the odour pollution was suggested in order to ensure control of concentration and intensity of the odour from the livestocks to maintain conducive living environment for the community.